Professionals’ Perceptions of Harm Arising from Medication Safety Incidents - Thompson, Keith (2022)
Objectives. To determine (1) the differences in healthcare professionals’ perception of actual and potential harm arising from medication safety incidents; (2) the impact of prescribing eligibility and advanced clinical practice on perception of harm; (3) the impact of training in assessing risk relating to medication safety incidents or errors on perception of harm; and (4) the impact of years’ experience on perception of harm.